2000
DOI: 10.1177/004051750007000107
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Properties of Pantyhose Fabric

Abstract: To clarify differences in the compressive properties of different kinds of pantyhose fabrics on the market in Japan, cylinder-elongation experiments and wear experiments are conducted, with Zokki, kohhen, sheer, wooly, and conjugate kinds of pantyhose are used as samples. Their compressive properties, which include compressive energy, compressive resilience, and fabric thickness, differ remarkably according to the types and the sites of hose and posture while being worn.We have been making fundamental studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…This can be attributed to the reduction in the mechanical restraint in the polyester fabric due to sericinand glutaraldehyde finishing. Morooka et al 27 concluded that a combination of CE and RC can reflectthe softness of the fabric. Higher CE values accompanied by lower RC values generally lead to a softer fabric.…”
Section: Resultsmentioning
confidence: 99%
“…This can be attributed to the reduction in the mechanical restraint in the polyester fabric due to sericinand glutaraldehyde finishing. Morooka et al 27 concluded that a combination of CE and RC can reflectthe softness of the fabric. Higher CE values accompanied by lower RC values generally lead to a softer fabric.…”
Section: Resultsmentioning
confidence: 99%
“…The pressure distributions of S-type and L-type knitted garment are shown in Fig. 8, (A, B, C), (4,5,6), and (1 0 , 2 0 , 3 0 ) are eight groups points set, and each group is composed of points on under bust-line, waistline and abdomen-line along vertical direction, obviously, the pressures which are measured on mannequin using S-type and L-type knitted garments are increasing along vertical down direction in each group except the last group. The size of abdomen-line of knitted garments should be amplified appropriately to increasing the comfort according to the size of mannequin.…”
Section: Pressure Measurement Of Knitted Garment On a Mannequinmentioning
confidence: 99%
“…Morooka et al [6] investigated the differences of the compressive properties between different kinds of pantyhose fabrics on the market in Japan, results showed their compressive properties, which include compressive energy, compressive resilience, and fabric thickness, differ remarkably according to the types and the sites of hose and posture while being worn. Harumi et al [7] performed a series of experiments for investigating the relationship of garment pressure and the physiological parameters such as heart rate, skin blood flow and respiratory function by utilizing a swimsuit.…”
Section: Introductionmentioning
confidence: 99%
“…The compressive effects of hosiery on a lower limb were considered to depend largely upon the elastic tensile strength (stretch) of the garment and the circumference of the limb at different levels [9,10]. By conducting cylinder-elongation experiments and wear experiments, Morooka et al found that the compressive properties of different kinds of hosieries fabrics (compressive energy, compressive resilience, and fabric thickness) differ markedly according to the types and the sites of hose and posture while being worn [11]. The mechanical properties of hosiery fabrics directly influenced their pressure magnitudes and distributions as well as corresponding therapeutic efficiencies.…”
Section: Introductionmentioning
confidence: 99%